Phased array antennas for mmWave frequency spectrum for 5G communication - Real, Shahriar Mohammad; Turjo, Rifat Rahman; Sobhan, Fabliha Fatema; Ashraf, Nabila (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.